Removal of ammonia from rubber wastewater using rubber-sludge-based biochar to enhance biogas production - NurulEzza Fazlina, Abu; Noor Yahida, Yahya; Fatin Zafirah, Mansur; Nurmunira, Muhammad (Elsevier, 2024)
Anaerobic digestion of rubber wastewater (ADRW) is an option for methane derivation for biogas production. However, the ammonia content in rubber wastewater, known as ammonia inhibition, has made the practical implementation of ADRW not yet feasible due to anaerobic digestion (AD) instability and low substrate degradation. Numerous studies have mentioned the use of biochar to overcome its inhibitory effect in AD. However, there are no report on the performance of rubber-sludge-based biochar (RSB) for removing ammonia from rubber wastewater to enhance biogas production. Therefore, this study investigates the potential of RSB to remove ammonia from wastewater to enhance biogas production. Initially, the RSB adsorbent was prepared by facile carbonization method and characterized with scanning electron microscopy (SEM), N2 physisorption, Fourier transform infrared (FTIR) spectroscopy, and elemental analysis. The performance of the RSB adsorbent for ammonia removal from wastewater was examined using the one -factor -at -one -time (OFAT) adsorption method. The AD process was then conducted using the treated wastewater. The results show that RSB possessed significant porous structure with high carbon content and a surface area of 20.3218 m2/g. The highest ammonia removal was 7.5 mg/l at an initial adsorbent loading dosage of 1.5 g of RSB for 30 min of mixing. Further, during the AD process, the highest biogas yield of 19.061 ml/g was achieved after 28 days at pH 8. Approximately 83 % of the methane composition was obtained from the biogas yield, indicating that the RSB contributes to the enhancement of biogas production by removing ammonia from rubber wastewater.